Islamic Religious Education Teachers' Strategies for Implementing a Digital Learning ‎Model in Teaching Rukhshah Material Using PDF Format at SMP Negeri 1 Bunguran ‎Utara, Natuna Regency, Riau Islands - Amaluddin Amaluddin; Suhari Suhari; Dewi Ferawati (Institute of Advanced Knowledge and Science, 2026)
This research is based on the development of information and communication technology in the digital era which has brought about enormous changes in various areas of life, including education. This research aims to obtain clear information about: 1) Planning of Islamic Religious Education teachers to apply digital learning models to rukhshah material. 2) Implementation of Islamic Religious Education teachers to apply digital learning models to rukhshah material. 3) Interaction between Islamic Religious Education teachers and students in implementing digital learning models to rukhshah material. The subjects of the study were Islamic religious education teachers, the principal, and students of SMP Negeri 1 Bunguran Utara, Natuna Regency, Riau Islands. To obtain data related to the research focus, the researcher conducted interviews, observations, and documentation. The data validity checking techniques used were: 1) Triangulation Technique, 2) Member Check Technique. The research results can be concluded: 1) Islamic Religious Education teachers' planning to implement a digital learning model for rukhshah material at SMP Negeri 1 Bunguran Utara, Natuna Regency, Riau Islands is carried out by teachers considering the readiness of facilities and infrastructure before the learning process is carried out. Teachers ensure that students have access to digital devices such as mobile phones or laptops and an adequate internet connection. In addition, teachers also adjust the learning platforms used, such as Google Classroom, WhatsApp Group, Zoom Meeting, or other applications that are easily accessible to students. 2) The implementation of Islamic Religious Education teachers applying digital learning models to the Rukhshah material at SMP Negeri 1 Bunguran Utara, Natuna Regency, Riau Islands, was carried out by implementing digital learning strategies on the Rukhshah material through the use of various digital media and platforms that support the learning process. The teacher conveyed that the implementation of the digital learning model aims to improve students' understanding of the Rukhshah material so that it is easier to understand, interesting, and in accordance with current technological developments. 3) Interaction between Islamic Religious Education teachers and students in implementing the digital learning model on the rukhshah material at SMP Negeri 1 Bunguran Utara, Natuna Regency, Riau Islands, namely the interaction between teachers and students in implementing the digital learning model on the rukhshah material takes place actively and communicatively. The teacher explained that the use of digital media helps create a more interesting learning atmosphere so that students more easily understand the material presented. Interactions do not only occur during face-to-face meetings in class, but also through digital learning media such as WhatsApp groups, Google Classroom, and learning videos.